ANALISIS TINGKAT KEBERHASILAN PENERAPAN SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH MELALUI MODEL DELONE AND MCLEANE - Arifiantika, Janis (Universitas Slamet Riyadi, 2015)
This research aims to analysis of success level in the implementation SIMKEUDA used to D&M model with research object at SKPD in Pemkot Semarang. There were 135 respondents participated software SIMKEUDA. In this research was quantitative method used primary data. The data collected was surveys mthod, direct observation method and questionnaires method, they data analyzed was used SEM at AMOS V.21. the result showed IS success D&M model was not significant fulfilled in the implementation of SIMKEUDA in Pemkot Semarang. Keywords: success model D & M, SIMKEUDA, SKPD